Informal Economic Education Based on Local Values of The Samin Society - Alifia Farisya Prima; Wahjoedi Wahjoedi; Agung Haryono (Journal of Applied Business, Taxation and Economics Research, 2023)
Informal education is important given to children from an early age. In informal education, there is a transfer of knowledge and transfer of cultural values. The purpose of this study is to analyze how Samin's local values colour the economic education given by parents to children. This study used a descriptive qualitative approach with ethnographic research. The research location was in the Japanese Hamlet, Margomulyo Village, Margomulyo District, Bojonegoro Regency, East Java. Source of data obtained through primary data and secondary data. Informants in the study were selected using a purposive sampling technique. Informants in this study were Samin community elders and parents who had school-age children in the Samin community. Data analysis includes the stages of data collection, data reduction, data presentation, conclusion and data verification. The results of the study are that education taught by parents in the family environment is based on the five noble speeches of Samin and local values that characterize economic education in the Samin community's family environment including the values of honesty, local values and the value of a sense of home that is instilled by parents in their children through example and habituation in everyday life.